Neisseria Gonorrhoeae Induced Disruption of Cell Junction Complexes in Epithelial Cells of the Human Genital Tract - Imarai-Bahamonde, C; Maisey-Munoz, K; Rodriguez-Tirado, F; Reyes-Cerpa, S (2012)
Pathogenic microorganisms, such as Neisseria gonorrhoeae, have developed mechanisms to alter epithelial barriers in order to reach subepithelial tissues for host colonization. The aim of this study was to examine the effects of gonococci on cell junction complexes of genital epithelial cells of women. Polarized Ishikawa cells, a cell line derived from endometrial epithelium, were used for experimental infection. Infected cells displayed a spindle-like shape with an irregular distribution, indicating potential alteration of cell-cell contacts. Accordingly, analysis by confocal microscopy and cellular fractionation revealed that gonococci induced redistribution of the adherens junction proteins E-cadherin and its adapter protein ?-catenin from the membrane to a cytoplasmic pool, with no significant differences in protein levels. In contrast, gonococcal infection did not induce modification of either expression or distribution of the tight junction proteins Occludin and ZO-1. Similar results were observed for Fallopian tube epithelia. Interestingly, infected Ishikawa cells also showed an altered pattern of actin cytoskeleton, observed in the form of stress fibers across the cytoplasm, which in turn matched a strong alteration on the expression of fibronectin, an adhesive glycoprotein component of extracellular matrix. Interestingly, using western blotting, activation of the ERK pathway was detected after gonococcal infection while p38 pathway was not activated. All effects were pili and Opa independent. Altogether, results indicated that gonococcus, as a mechanism of pathogenesis, induced disruption of junction complexes with early detaching of E-cadherin and ?-catenin from the adherens junction complex, followed by a redistribution and reorganization of actin cytoskeleton and fibronectin within the extracellular matrix. © 2011 .